Toll-like receptor 2 is critical for induction of Reg3β expression and intestinal clearance of Yersinia pseudotuberculosis. Issue 6 (27th January 2009) - Dessein, R; Gironella, M; Vignal, C; Peyrin-Biroulet, L; Sokol, H; Secher, T; Lacas-Gervais, S; Gratadoux, J-J; Lafont, F; Dagorn, J-C; Ryffel, B; Akira, S; et al.
Abstract : Objective: Yersinia pseudotuberculosis causes ileitis and mesenteric lymphadenitis by mainly invading the Peyer's patches that are positioned in the terminal ileum. Whereas toll-like-receptor 2 (TLR2) controls mucosal inflammation by detecting certain microbiota-derived signals, its exact role in protecting Peyer's patches against bacterial invasion has not been defined. Design: Wild-type, Tlr2 -, Nod2 - and MyD88 -deficient animals were challenged by Y pseudotuberculosis via the oral or systemic route. The role of microbiota in conditioning Peyer's patches against Yersinia through TLR2 was assessed by delivering, ad libitum, exogenous TLR2 agonists in drinking water to germ-free and streptomycin-treated animals. Bacterial eradication from Peyer's patches was measured by using a colony-forming unit assay. Expression of cryptdins and the c-type lectin Reg3β was quantified by quantitative reverse transcriptase polymerase chain reaction analysis. Results: Our data demonstrated that Tlr2 -deficient mice failed to limit Yersinia dissemination from the Peyer's patches and succumbed to sepsis independently of nucleotide-binding and oligomerisation domain 2 (NOD2). Recognition of both microbiota-derived and myeloid differentiation factor 88 (MyD88)-mediated elicitors was found to be critically involved in gut protection against Yersinia -induced lethality, while TLR2 was dispensable to systemic Yersinia infection. Gene expression analyses revealed that optimal epithelial transcript level of the anti-infective Reg3β requires TLR2 activation. Consistently, Yersinia infection triggered TLR2-dependent Reg3β expression in Peyer's patches. Importantly, oral treatment with exogenous TLR2 agonists in germ-free animals was able to further enhance Yersinia -induced expression of Reg3β and to restore intestinal resistance to Yersinia . Lastly, genetic ablation of Reg3β resulted in impaired clearance of the bacterial load in Peyer's patches. Conclusions: TLR2/REG3β is thus an essential component in conditioning epithelial defence signalling pathways against bacterial invasion.